(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The role of counterfeit goods in the industrial industries has grown in recent years. Name recognition, sales, and bottom line results are all impacted. Authentic products can be located and counterfeit goods can be identified with the use of blockchain technology. Distributed ledger technology, also known as blockchain, is a digital system that records transactions in a decentralised database using a system of interconnected blocks. Since blockchain technology is impenetrable, no one block can be altered or compromised. Customers and users can verify the safety of a product without depending on other users thanks to blockchain technology. As mobile and wireless technologies continue to evolve, this investigation finds that rapid response (QR) codes offer a strong tool in the fight against product counterfeiting. Using a QR code scanner that is connected to a blockchain can help identify counterfeit products. One possible usage of this system is to create unique codes for products and store them in the database as blocks. It takes the user’s one-of-a-kind code and checks it against records in the blockchain ledger. A notification will be sent to the consumer if the code matches. In any other case, the buyer will be alerted that the goods is counterfeit.